2018
DOI: 10.4103/jfmpc.jfmpc_99_18
|View full text |Cite
|
Sign up to set email alerts
|

Joint position statement Indian association of palliative care and academy of family physicians of India – The way forward for developing community-based palliative care program throughout India: Policy, education, and service delivery considerations

Abstract: Purpose:This joint position statement, by the Indian Association of Palliative Care (IAPC) and Academy of Family Physicians of India (AFPI), proposes to address gaps in palliative care provision in the country by developing a community-based palliative care model that will empower primary care physicians to provide basic palliative care.Evidence:India ranks very poorly, 67th of 80 countries in the quality of death index. Two-thirds of patients who die need palliative care and many such patients spend the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…To overcome these challenges, an integrated community palliative care model was suggested jointly by Indian Association of Palliative Care (IAPC) and Association of Family Physicians of India (AFPI). Subsequently, the associations jointly published a position paper[15] in 2018 emphasising the importance of incorporating primary palliative care into the routine clinical practice of PCP/FP and another paper in 2019[16] deliberating on the competency framework necessary for PCP/FP to provide primary palliative care in the community. The integrated model can have variations in its nature and application, however a systematic review investigating the integrated model identified five core aspects of a successful model.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these challenges, an integrated community palliative care model was suggested jointly by Indian Association of Palliative Care (IAPC) and Association of Family Physicians of India (AFPI). Subsequently, the associations jointly published a position paper[15] in 2018 emphasising the importance of incorporating primary palliative care into the routine clinical practice of PCP/FP and another paper in 2019[16] deliberating on the competency framework necessary for PCP/FP to provide primary palliative care in the community. The integrated model can have variations in its nature and application, however a systematic review investigating the integrated model identified five core aspects of a successful model.…”
Section: Discussionmentioning
confidence: 99%
“…One of the crucial recommendations is the joint statement of the Indian Association of Palliative Care and the Academy of Family Physicians of India to integrate palliative care at all levels of healthcare and liaise with general practitioners and family physicians. 26…”
Section: Discussionmentioning
confidence: 99%
“…Ressalta-se que a educação e o treinamento em CP devem estar disponíveis e acessíveis a médicos, enfermeiros, farmacêuticos, sioterapeutas, terapeutas ocupacionais, fonoaudiólogos, assistentes sociais, capelães e trabalhadores espirituais; e toda equipe multipro ssional e fazer parte do currículo pro ssional nos níveis de graduação e pósgraduação (17) .…”
Section: Discussionunclassified